(untitled) (Research, Society and Development, 2021)
Introduction: Fall is a public health problem and the identification of associated factors constitutes an important strategy in health prevention. Objective: To identify the frequency of falls and associated factors among elderly people enrolled in a Basic Health Unit (BHU). Methodology: A cross-sectional study carried out in BHU in the city of Petrolina, PE (Brazil) involving 40 elderly people aged ≥60 years. Socioeconomic assessment, general health status, and history of falls, and fear of falling were assessed by structured questionnaires. The Mini-Mental State Examination (MMSE) was used as an indicator of cognitive function and the Timed Up and Go (TUG) was used to assess the risk of fall. An anthropometric assessment was also performed. The distribution of absolute and relative frequencies was calculated with confidence intervals at 95% (CI95%). Associations between the occurrence of falls and the other variables were calculated using the Chi-square or Fisher’s exact tests. Results: 38 elderly people were included, with a median age of 68.5 years, 42.1% (n=16) had a history of at least one fall in the last 12 months and 21.1% (n=8) failed to perform any activity for fear of falling. There were no significant associations between the occurrence of falls and the variables age, sex, diabetes mellitus, systemic arterial hypertension, risk of fall, fear of falling, visual impairment, and osteoarticular disease. Conclusion: The frequency of falls was high among the elderly analyzed and no significant associations were verified between the occurrence of falls and the predictive factors.